Bioactive Silicate Nanoplatelets for Osteogenic Differentiation of Human Mesenchymal Stem Cells. (13th May 2013) - Gaharwar, Akhilesh K.; Mihaila, Silvia M.; Swami, Archana; Patel, Alpesh; Sant, Shilpa; Reis, Rui L.; Marques, Alexandra P.; Gomes, Manuela E.; Khademhosseini, Ali
<x xml:space="preserve">Abstract</x> Novel silicate nanoplatelets that induce osteogenic differentiation of human mesenchymal stem cells (hMSCs) in the absence of any osteoinductive factor are reported. The presence of the silicate triggers a set of events that follows the temporal pattern of osteogenic differentiation. These findings underscore the potential applications of these silicate nanoplatelets in designing bioactive scaffolds for musculoskeletal tissue engineering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>